Prevalence and predictors for lipodystrophy syndrome among HIV infected children on anti-retroviral therapy - G. N., Sanjeeva; H. B., Pavithra; V., Sukanya; S., Shobha; M., Govindaraj (International Journal of Contemporary Pediatrics, 2016)
Background: With the widespread use of ART and prolonged survival of CLHIV, toxicities like lipodystrophy are increasingly evident. There are limited pediatric data on the prevalence of Lipodystrophy syndrome (LDS). The aim of this study was to determine the prevalence and predictors associated with LDS among HIV-infected children on ART. Methods: A cross-sectional study of 320 CLHIV aged between 2-18 years on ART were enrolled. Fat redistribution (FR) was assessed clinically and fasting blood sample was taken for lipid profile. LDS was defined as FR or metabolic abnormalities or both. We conducted univariate, multivariate and adjusted analysis to determine factors predisposing to LDS. Results: Median age of the participants was 13 years. Mean duration on ART was 3.7±1.9 years. Prevalence of LDS, FR, and metabolic abnormalities was 60%, 46% and 36% respectively. We found significant association between FR and age less than 5 yrs at the time of ART initiation, d4T exposure and duration of ART exposure of > 3yrs. Children who were moderately malnourished before ART initiation were less likely to develop FR and LDS (p=0.03). A significant association was also seen between metabolic abnormalities and female gender, advanced sexual maturity and hypertriglyceridemia at the time of ART initiation. Conclusions: Prevalence of LDS is high among HIV-infected children on ART and likelihood of developing FR increases with prolonged exposure of ART as well as early age of initiation of ART. Advanced sexual maturation and hypertriglyceridemia at the time of ART initiation were associated with increased prevalence of metabolic abnormalities.